2010
DOI: 10.1007/s11606-010-1524-5
|View full text |Cite
|
Sign up to set email alerts
|

Gut Feelings as a Third Track in General Practitioners’ Diagnostic Reasoning

Abstract: BackgroundGeneral practitioners (GPs) are often faced with complicated, vague problems in situations of uncertainty that they have to solve at short notice. In such situations, gut feelings seem to play a substantial role in their diagnostic process. Qualitative research distinguished a sense of alarm and a sense of reassurance. However, not every GP trusted their gut feelings, since a scientific explanation is lacking.ObjectiveThis paper explains how gut feelings arise and function in GPs’ diagnostic reasonin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
194
0
10

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(208 citation statements)
references
References 69 publications
(92 reference statements)
4
194
0
10
Order By: Relevance
“…The GP's gut feeling is, and we agree with Stolper et al (2011), a very important and complex issue in GP practice. Their findings and descriptions are very interesting and of great significance when studying GP clinical practice and GP training.…”
Section: Dear Sirsupporting
confidence: 57%
“…The GP's gut feeling is, and we agree with Stolper et al (2011), a very important and complex issue in GP practice. Their findings and descriptions are very interesting and of great significance when studying GP clinical practice and GP training.…”
Section: Dear Sirsupporting
confidence: 57%
“…18,19 This contextual information feeds into both analytical and non-analytical diagnostic reasoning. 20 Most GPs regarded the first patient impression as an important element. Studies mainly conducted with simulated patients showed how different patient characteristics influenced physician's behaviour.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Stolper et al confirm the important role of gut feelings together with analytical reasoning and personal experience in GPs' diagnostic reasoning. 20 The initial steps of the diagnostic process are often non-analytical or intuitive 24 before, in a further step, one or several hypotheses are generated. 25 This process is reflected in these data.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…There is current interest in the physician's gut feeling 12 based on the hypothesis that analytical and non-analytical processes interact during the doctor's diagnostic work. 13 However, gut feeling sometimes may be based on clinical observations rather than vague impressions, that is, general appearance, breathing pattern, and weight loss.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%